Divergent Development experiences: A general outlook of China and Latin America’s Development trends - Cortes Rondoy, Jael (Latin American Journal of Trade Policy, 2022)
Following a definition of development that brings back the role of productive capabilities and endorses structural change, this paper examines two key elements and their trends: industrialization and trade patterns. Through the analysis of economic factors covering the period 1980-2019, this paper aims to offer insights into the elements that have led to divergent development outcomes in China and Latin America, paying particular attention to the cases of Chile and Mexico. Indicators including yearly GDP growth, the share of the world GDP, and per-capita GDP will be used to show that China has outpaced Latin America in terms of growth. Moreover, it will also be demonstrated that while Latin America is experiencing a deindustrialization trend, evidenced by a decline in the manufacturing sector and low levels of high-technology exports, China has experienced rapid industrialization. Moreover, China’s exports serve as an illustration of a country that transitioned from producing and exporting low-value manufactured items to more complex goods with higher added value, while Chile has not been able to leave behind its reliance on natural resources. In the case of Mexico, although its exports are not concentrated in primary commodities, they are built on a maquiladora model that relegates it to the bottom of industrial value chains.